Factors that influence the effectiveness of online advertising in enhancing consumer's purchase intention among young adults in Malaysia - Izian Idris, *; Siti Suhana, A. *; Ahmad, A.; Lim, Serena Kai Xin (The Mattingley Publishing Co., Inc, 2020)
The advertising industry is seeing growth for online advertising, where it has now exceeded the performance of TV advertising. However, the advertising industry in Malaysia still relies heavily on traditional forms of advertising. This paper therefore aims to determine the factors that might affect the effectiveness of online advertising in enhancing consumers' purchase intention. As young adults are more exposed to online advertising as compared to other age groups, convenience sampling is applied to approach Millennials around the city areas of Malaysia. A sample size of 300 respondents is selected for this study to ensure that the data accuracy is acceptable. Furthermore, the hierarchy of effects model and the source credibility theory are applied to study the effects of online advertising towards young adults in Malaysia. The results show that there are significant relationships between the advertising appeal (emotional), credibility of endorser, and the exposure rate of online advertisements with consumers' purchase intention. However, it was found that the creativity of online advertisements does not have a relationship with consumers' purchase intention. This study helps local marketers and advertisers to strategize more effective online advertising campaigns that better attract the attention of young adults and influence their purchase intention.